Perovskite type mixed conductor material, perovskite type mixed conductor hydrogen permeable membrane and preparation method and application thereof
By doping transition metal elements into perovskite-type mixed conductor materials, a hydrogen permeable film with stable and high conductivity under a reducing atmosphere was prepared, which solved the poor stability and poor stability of the traditional perovskite-type separation film under a reducing atmosphere. The problem of low conductivity improves the hydrogen separation performance.
Patent Information
- Application Number
- CN202310738150.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-20
AI Technical Summary
Traditional perovskite separation membranes have poor stability and low proton-electron conductivity under reducing atmosphere, which cannot meet the industrial application requirements of hydrogen separation.
Using the perovskite hybrid conductor material BaZr0.1Ce0.7Y0.1Yb0.1O3-δ, the structure stable and stable under a reducing atmosphere was prepared by doping transition metal elements such as Fe, Co, and Ni in the perovskite structure. Proton-Hydrogen permeable membrane with high electron conductivity.
The structural stability and high proton-electronic conductor hydrogen permeable film are achieved under a reducing atmosphere, which improves the hydrogen separation performance and meets the needs of industrial applications.
Smart Images

Figure CN116751058B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy separation material application, and in particular to a perovskite type mixed conductor material, a perovskite type mixed conductor hydrogen permeable membrane, and a preparation method and application thereof. Background Art
[0002] Problems such as pollution and energy shortages have forced the main energy source to shift from traditional fossil fuels to new clean energy. In the hydrogen-based hydrogen energy industry, hydrogen separation and purification are important components. Traditional dense membrane materials for hydrogen separation lack proton conductivity or electron conductivity, resulting in their hydrogen separation performance failing to meet the requirements of practical industrial applications. Perovskite separation membranes have good stability in hydrogen environments, high mechanical strength, simple separation operations, low membrane material cost, and low energy consumption. Moreover, the proton-electron conductive membrane based on the perovskite oxide structure can separate and purify hydrogen from the mixed gas produced by industrial-scale steam reforming, and therefore has received widespread attention.
[0003] However, traditional perovskite separation membranes have poor stability in reducing atmospheres and low proton-electron conductivity. Summary of the invention
[0004] Based on this, it is necessary to provide a perovskite-type mixed conductor material suitable for hydrogen separation membrane and a preparation method thereof. The perovskite-type mixed conductor hydrogen permeable membrane prepared using the perovskite-type mixed conductor material has a stable structure under a reducing atmosphere, high proton-electron conductivity, and good hydrogen permeability.
[0005] In one aspect of the present application, a perovskite-type mixed conductor material is provided, wherein the chemical formula of the perovskite-type mixed conductor material is BaZr a Ce b Y c Yb d X e O 3-δ , wherein X is one or more transition metal elements Fe, Co, Ni, Cu, Zn, a+b+c+d+e=1, and δ is 0 to 0.5.
[0006] In one embodiment, the chemical formula of the perovskite mixed conductor material is Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 1-y X y O 3-δ , where y is 0.05 to 0.2.
[0007] In another aspect of the present application, a method for preparing the perovskite-type mixed conductor material is provided, comprising the following steps:
[0008] Providing precursors;
[0009] The precursor is sintered to prepare the perovskite-type mixed conductor material.
[0010] In one embodiment, the sintering temperature is 800° C. to 1150° C.; and / or the sintering time is 5 h to 20 h; and / or the sintering atmosphere is air.
[0011] In one embodiment, the method for preparing the precursor comprises the following steps:
[0012] The precursor is prepared by weighing raw materials according to the chemical formula, ball milling, and drying. The raw materials include one or more of barium carbonate, zirconium oxide, yttrium oxide, ytterbium oxide, and cerium oxide.
[0013] In one embodiment, the rotation speed of the ball mill is 300 rpm to 400 rpm.
[0014] In one embodiment, the drying temperature is 70°C to 100°C.
[0015] In another aspect of the present application, a method for preparing a perovskite-type mixed conductor hydrogen permeable membrane is provided, comprising the following steps:
[0016] The perovskite type mixed conductor material is pressed into sheets and sintered to prepare the perovskite type mixed conductor film.
[0017] In another aspect of the present application, a perovskite-type mixed conductor hydrogen permeable membrane is provided, which is prepared by the method described above.
[0018] In another aspect of the present application, there is provided a use of the perovskite type mixed conductor material or the perovskite type mixed conductor hydrogen permeable membrane in the preparation of a hydrogen separation membrane.
[0019] The perovskite mixed conductor material BaZr provided in this application 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ By doping transition metal elements at the B position of the perovskite structure and using specific transition metal elements and doping ratios, it is possible to prepare a perovskite-type mixed conductor hydrogen permeable membrane, which has a stable structure under a reducing atmosphere, high proton-electron conductivity, and good hydrogen permeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The perovskite mixed conductor material Ba(Zr) of one embodiment 0.1 Ce 0.7 Y0.1 Yb 0.1 ) 0.9 Ni 0.1 O 3-δ XRD pattern of
[0021] Figure 2 The perovskite mixed conductor material Ba(Zr) of one embodiment 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Ni 0.1 O 3-δ SEM images of
[0022] Figure 3 The perovskite mixed conductor material Ba(Zr) of one embodiment 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Ni 0.1 O 3-δ Hydrogen permeability at 650℃~800℃ in 10%H2-90%He atmosphere;
[0023] Figure 4 The perovskite mixed conductor material Ba(Zr) of one embodiment 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Co 0.1 O 3-δ XRD pattern of
[0024] Figure 5 The perovskite mixed conductor material Ba(Zr) of one embodiment 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Co 0.1 O 3-δ SEM images of
[0025] Figure 6 The perovskite mixed conductor material Ba(Zr) of one embodiment 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Co 0.1 O 3-δ Hydrogen permeability at 650℃~800℃ in 10%H2-90%He atmosphere;
[0026] Figure 7The perovskite mixed conductor material Ba(Zr) of one embodiment 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Fe 0.1 O 3-δ XRD pattern of
[0027] Figure 8 The perovskite mixed conductor material Ba(Zr) of one embodiment 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Fe 0.1 O 3-δ SEM images of
[0028] Fig. 9 The perovskite mixed conductor material Ba(Zr) of one embodiment 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Fe 0.1 O 3-δ Hydrogen permeability at 650℃~800℃ in 10%H2-90%He atmosphere;
[0029] Fig.10 For some embodiments of the perovskite mixed conductor material Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 1-y Ni y O 3-δ Hydrogen permeability at 650°C to 800°C in a 10% H2-90% He atmosphere, where y = 0.05, 0.10, 0.15 and 0.20;
[0030] Fig.11 For some embodiments of the perovskite mixed conductor material Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 1-y Ni y O 3-δ Hydrogen permeability in 10% H2-90% He atmosphere at 600°C to 800°C, wherein y=0.05, 0.10, 0.15 and 0.20. DETAILED DESCRIPTION
[0031] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0033] In one aspect of the present application, a perovskite-type mixed conductor material is provided, wherein the chemical formula of the perovskite-type mixed conductor material is BaZr a Ce b Y c Yb d X e O 3-δ , wherein X is one or more transition metal elements Fe, Co, Ni, Cu, Zn, a+b+c+d+e=1, and δ is 0 to 0.5.
[0034] In one example, the chemical formula of the perovskite mixed conductor material is Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 1-y X y O 3-δ , where y is 0.05 to 0.2.
[0035] In another aspect of the present application, a method for preparing the perovskite-type mixed conductor material is provided, comprising the following steps:
[0036] Providing precursors;
[0037] The precursor is sintered to prepare the perovskite-type mixed conductor material.
[0038] In one example, the sintering temperature is 800°C to 1150°C.
[0039] In one example, the sintering time is 5 hours to 20 hours.
[0040] In one example, the sintering atmosphere is air.
[0041] In one example, the method for preparing the precursor comprises the following steps:
[0042] The precursor is prepared by weighing raw materials according to the chemical formula, ball milling, and drying. The raw materials include one or more of barium carbonate, zirconium oxide, yttrium oxide, ytterbium oxide, and cerium oxide.
[0043] In one example, the rotation speed of the ball mill is 300 rpm to 400 rpm.
[0044] In one example, the drying temperature is 70°C to 100°C.
[0045] In another aspect of the present application, a method for preparing a perovskite-type mixed conductor hydrogen permeable membrane is provided, comprising the following steps:
[0046] The perovskite type mixed conductor material is pressed into sheets and sintered to prepare the perovskite type mixed conductor film.
[0047] In another aspect of the present application, a perovskite-type mixed conductor hydrogen permeable membrane is provided, which is prepared by the method described above.
[0048] In another aspect of the present application, there is provided a use of the perovskite type mixed conductor material or the perovskite type mixed conductor hydrogen permeable membrane in the preparation of a hydrogen separation membrane.
[0049] The perovskite mixed conductor material BaZr provided in this application 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ By doping transition metal elements at the B position of the perovskite structure and using specific transition metal elements and doping ratios, it is possible to prepare a perovskite-type mixed conductor hydrogen permeable membrane, which has a stable structure under a reducing atmosphere, high proton-electron conductivity, and good hydrogen permeability.
[0050] The perovskite mixed conductor material, the perovskite mixed conductor hydrogen permeable membrane and the preparation method thereof of the present application are further described below through specific examples.
[0051] Embodiment 1:
[0052] The preparation process of the perovskite type mixed conductor material and the perovskite type mixed conductor hydrogen permeable membrane of this embodiment is as follows:
[0053] 1. According to the chemical formula Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Ni 0.1 O 3-δ(δ=0.5) Weigh 1.9734 g of barium carbonate, 1.2322 g of zirconium oxide, 1.7211 g of cerium oxide, 2.2581 g of yttrium oxide, 3.9408 g of ytterbium oxide and 0.7469 g of nickel oxide in corresponding stoichiometric proportions, put them into a ball mill, add ethanol, ball mill at a speed of 350 rpm for 20 hours, and dry at 80°C to obtain a precursor.
[0054] 2. The above precursor was placed in a crucible, placed in a muffle furnace, sintered at 1000°C in an air atmosphere for 5 hours, and taken out after cooling to obtain a perovskite-type mixed conductor material Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Ni 0.1 O 3-δ .
[0055] 3. The perovskite type mixed conductor material is pressed into sheets and sintered at 1400° C. for 10 hours to obtain a perovskite type mixed conductor hydrogen permeable membrane.
[0056] The performance test process of the perovskite mixed conductor material and the perovskite mixed conductor hydrogen permeable membrane is as follows:
[0057] 1. XRD test: The perovskite mixed conductor material was tested using a German Bruker D8Advance diffractometer with a scanning angle range of 2θ = 20° to 80°, a scanning speed of 5° / min, and a scanning step of 0.015°. The XRD spectrum was obtained as follows: Figure 1 As shown. Figure 1 It can be seen that the product prepared in this example is Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Ni 0.1 O 3-δ Crystal phase.
[0058] 2. SEM test: The perovskite mixed conductor material was observed using a German Zeiss Cross Beam 540 scanning electron microscope. 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Ni 0.1 O 3-δ The particle morphology and element distribution of the powder are as follows: Figure 2 As shown. Figure 2 It can be seen that the grains of the perovskite-type mixed conductor material are complete.
[0059] 3. Hydrogen permeability test: The atmosphere on the feed side is 10% H2-90% He, the atmosphere on the purge side is pure nitrogen, the test temperature is 650℃~800℃, the test results are as follows Figure 3 shown.
[0060] Embodiment 2:
[0061] The preparation process of the perovskite type mixed conductor material and the perovskite type mixed conductor hydrogen permeable membrane of this embodiment is as follows:
[0062] 1. According to the chemical formula Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Co 0.1 O 3-δ (δ=0.5) Weigh 1.9734 g of barium carbonate, 1.2322 g of zirconium oxide, 1.7211 g of cerium oxide, 2.2581 g of yttrium oxide, 3.9408 g of ytterbium oxide and 2.408 g of cobalt oxide in corresponding stoichiometric proportions, put them into a ball mill, add ethanol, ball mill at a speed of 350 rpm for 20 hours, and dry at 80°C to obtain a precursor.
[0063] 2. The above precursor was placed in a crucible, placed in a muffle furnace, sintered at 1000°C in an air atmosphere for 5 hours, and taken out after cooling to obtain a perovskite-type mixed conductor material Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Co 0.1 O 3-δ .
[0064] 3. The perovskite type mixed conductor material is pressed into sheets and sintered at 1400° C. for 10 hours to obtain a perovskite type mixed conductor hydrogen permeable membrane.
[0065] The performance test process of the perovskite mixed conductor material and the perovskite mixed conductor hydrogen permeable membrane is as follows:
[0066] 1. XRD test: The perovskite-type mixed conductor material was tested using a German Bruker D8 Advance diffractometer with a scanning angle range of 2θ = 20° to 80°, a scanning speed of 5° / min, and a scanning step of 0.015°. The XRD spectrum was obtained as follows: Figure 4 As shown. Figure 4 It can be seen that the product prepared in this example is Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9Co 0.1 O 3-δ Crystal phase.
[0067] 2. SEM test: The perovskite mixed conductor material was observed using a German Zeiss Cross Beam 540 scanning electron microscope. 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Co 0.1 O 3-δ The particle morphology and element distribution of the powder are as follows: Figure 5 As shown. Figure 5 It can be seen that the grains of the perovskite-type mixed conductor material are complete.
[0068] 3. Hydrogen permeability test: The atmosphere on the feed side is 10% H2-90% He, the atmosphere on the purge side is pure nitrogen, the test temperature is 650℃~800℃, the test results are as follows Figure 6 shown.
[0069] Embodiment 3:
[0070] The preparation process of the perovskite type mixed conductor material and the perovskite type mixed conductor hydrogen permeable membrane of this embodiment is as follows:
[0071] 1. According to the chemical formula Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Fe 0.1 O 3-δδ (δ=0.5) Weigh 1.9734 g of barium carbonate, 1.2322 g of zirconium oxide, 1.7211 g of cerium oxide, 2.2581 g of yttrium oxide, 3.9408 g of ytterbium oxide and 1.5969 g of iron oxide in corresponding stoichiometric ratios, put them into a ball mill, add ethanol, ball mill at a speed of 350 rpm for 20 hours, and dry at 80°C to obtain a precursor.
[0072] 2. The above precursor was placed in a crucible, placed in a muffle furnace, sintered at 1000°C in an air atmosphere for 5 hours, and taken out after cooling to obtain a perovskite-type mixed conductor material Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Fe 0.1 O 3-δ .
[0073] 3. The perovskite type mixed conductor material is pressed into sheets and sintered at 1400° C. for 10 hours to obtain a perovskite type mixed conductor hydrogen permeable membrane.
[0074] The performance test process of the perovskite mixed conductor material and the perovskite mixed conductor hydrogen permeable membrane is as follows:
[0075] 1. XRD test: The perovskite-type mixed conductor material was tested using a German Bruker D8 Advance diffractometer with a scanning angle range of 2θ = 20° to 80°, a scanning speed of 5° / min, and a scanning step of 0.015°. The XRD spectrum was obtained as follows: Figure 7 As shown. Figure 7 It can be seen that the product prepared in this example is Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Fe 0.1 O 3-δ Crystal phase.
[0076] 2. SEM test: The perovskite mixed conductor material was observed using a German Zeiss Cross Beam 540 scanning electron microscope. 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Fe 0.1 O 3-δ The particle morphology and element distribution of the powder are as follows: Figure 8 As shown. Figure 8 It can be seen that the grains of the perovskite-type mixed conductor material are complete.
[0077] 3. Hydrogen permeability test: The atmosphere on the feed side is 10% H2-90% He, the atmosphere on the purge side is pure nitrogen, the test temperature is 650℃~800℃, the test results are as follows Fig. 9 shown.
[0078] Embodiment 4:
[0079] The preparation process of the perovskite type mixed conductor material and the perovskite type mixed conductor hydrogen permeable membrane of this embodiment is as follows:
[0080] 1. According to the chemical formula Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.95 Ni 0.05 O 3-δ(δ=0.5) Weigh barium carbonate, zirconium oxide, cerium oxide, yttrium oxide, ytterbium oxide and nickel oxide in corresponding stoichiometric ratios, put them into a ball mill, add ethanol, ball mill at a speed of 350 rpm for 20 hours, and dry at 80°C to obtain a precursor.
[0081] 2. The above precursor was placed in a crucible, placed in a muffle furnace, sintered at 1000°C in an air atmosphere for 5 hours, and taken out after cooling to obtain a perovskite-type mixed conductor material Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.95 Ni 0.05 O 3-δ .
[0082] 3. The perovskite type mixed conductor material is pressed into sheets and sintered at 1400° C. for 10 hours to obtain a perovskite type mixed conductor hydrogen permeable membrane.
[0083] Embodiment 5:
[0084] The preparation process of the perovskite type mixed conductor material and the perovskite type mixed conductor hydrogen permeable membrane of this embodiment is as follows:
[0085] 1. According to the chemical formula Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.85 Ni 0.15 O 3-δ (δ=0.5) Weigh barium carbonate, zirconium oxide, cerium oxide, yttrium oxide, ytterbium oxide and nickel oxide in corresponding stoichiometric ratios, put them into a ball mill, add ethanol, ball mill at a speed of 350 rpm for 20 hours, and dry at 80°C to obtain a precursor.
[0086] 2. The above precursor was placed in a crucible, placed in a muffle furnace, sintered at 1000°C in an air atmosphere for 5 hours, and taken out after cooling to obtain a perovskite-type mixed conductor material Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.85 Ni 0.15 O 3-δ .
[0087] 3. The perovskite type mixed conductor material is pressed into sheets and sintered at 1400° C. for 10 hours to obtain a perovskite type mixed conductor hydrogen permeable membrane.
[0088] Embodiment 6:
[0089] The preparation process of the perovskite type mixed conductor material and the perovskite type mixed conductor hydrogen permeable membrane of this embodiment is as follows:
[0090] 1. According to the chemical formula Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.8 Ni 0.2 O 3-δ (δ=0.5) Weigh barium carbonate, zirconium oxide, cerium oxide, yttrium oxide, ytterbium oxide and nickel oxide in corresponding stoichiometric ratios, put them into a ball mill, add ethanol, ball mill at a speed of 350 rpm for 20 hours, and dry at 80°C to obtain a precursor.
[0091] 2. The above precursor was placed in a crucible, placed in a muffle furnace, sintered at 1000°C in an air atmosphere for 5 hours, and taken out after cooling to obtain a perovskite-type mixed conductor material Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.8 Ni 0.2 O 3-δ .
[0092] 3. The perovskite type mixed conductor material is pressed into sheets and sintered at 1400° C. for 10 hours to obtain a perovskite type mixed conductor hydrogen permeable membrane.
[0093] The performance of the perovskite-type mixed conductor hydrogen permeable membranes prepared in Examples 1 and 4 to 6 was tested, and the specific process is as follows:
[0094] 1. Hydrogen permeability test: The hydrogen permeability of the perovskite-type mixed conductor hydrogen permeable membrane was tested using a gas chromatograph of model GC-2060. The atmosphere on the feed side was 10% H2-90% He, and the atmosphere on the purge side was pure nitrogen. The test temperature was 650°C to 800°C. The test results are as follows: Fig.10 shown.
[0095] 2. Proton-electron conductivity test: The proton-electron conductivity of the perovskite-type mixed conductor hydrogen permeable membrane was tested using the Swiss Metrohm Autolab electrochemical workstation. The test atmosphere was pure hydrogen and the temperature was 600℃~800℃. The test results are as follows: Fig.11 shown.
[0096] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0097] The above-described embodiments only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in detail, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the attached claims described in the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description can be used to interpret the contents of the claims.
Claims
1. A perovskite-type mixed conductor material for hydrogen separation membrane, characterized in that: The chemical formula of the perovskite mixed conductor material is Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 1-y X y O 3-δ , wherein X is the transition metal element Fe, y is 0.1; and δ is 0 to 0.
5.
2. The method for preparing the perovskite-type mixed conductor material for hydrogen separation membrane according to claim 1, characterized in that: The steps include: Providing precursors; The precursor is sintered to prepare the perovskite-type mixed conductor material for hydrogen separation membrane.
3. The method for preparing a perovskite-type mixed conductor material for a hydrogen separation membrane according to claim 2, characterized in that: The sintering temperature is 800° C. to 1150° C.; and / or the sintering time is 5 h to 20 h; and / or the sintering atmosphere is air.
4. The method for preparing a perovskite-type mixed conductor material for a hydrogen separation membrane according to claim 2, characterized in that: The preparation method of the precursor comprises the following steps: The precursor is prepared by weighing raw materials according to the chemical formula, ball milling, and drying. The raw materials include one or more of barium carbonate, zirconium oxide, yttrium oxide, ytterbium oxide, and cerium oxide.
5. The method for preparing a perovskite-type mixed conductor material for a hydrogen separation membrane according to claim 4, characterized in that: The rotation speed of the ball mill is 300 rpm to 400 rpm.
6. The method for preparing a perovskite-type mixed conductor material for a hydrogen separation membrane according to claim 4, characterized in that: The drying temperature is 70°C to 100°C.
7. A method for preparing a perovskite-type mixed conductor hydrogen permeable membrane, characterized in that: The following steps are involved: The perovskite type mixed conductor material for hydrogen separation membrane as claimed in claim 1 is tableted and sintered to prepare the perovskite type mixed conductor membrane.
8. A perovskite-type mixed conductor hydrogen permeable membrane, characterized in that: The method according to claim 7 is used to prepare it.
9. Use of the perovskite type mixed conductor material for hydrogen separation membrane according to claim 1 or the perovskite type mixed conductor hydrogen permeable membrane according to claim 8 in the preparation of hydrogen separation membrane.